Materials design of sodium chloride solid electrolytes Na3MCl6 for all-solid-state sodium-ion batteries - Park, Dongsu; Kim, Kwangnam; Chun, Gin Hyung; Wood, Brandon C.; Shim, Joon Hyung; Yu, Seungho (Royal Society of Chemistry, 2021)
All-solid-state sodium-ion batteries have attracted increasing attention owing to the low cost of sodium and the enhanced safety compared to conventional Li-ion batteries. Recently, halides have been considered as promising solid electrolytes (SEs) due to their favorable combination of high ionic conductivity and chemical stability against high-voltage cathode materials. Although a wide variety of lithium chloride SEs, Li3MCl6, have been developed for high-voltage all-solid-state batteries, only a limited number of sodium chloride SEs have been reported. This study aims to offer a material design insight for the development of sodium chloride SEs through systematic assessment of the phase stability, electrochemical stability, and transport properties of novel Na3MCl6 SEs. Structural calculations indicate that Na3MCl6 exhibits trigonal P31c, monoclinic P2(1)/n, and trigonal R3 phases, and the stable phase of Na3MCl6 is dependent on the type and ionic radius of M. Na3MCl6 typically exhibits a high oxidation potential, demonstrating good electrochemical stability against cathodes. The bond-valence site energy and ab initio molecular dynamics calculations revealed that Na3MCl6 with P2(1)/n and R3 phases showed low ionic conductivity, while the P31c phase slightly improved the ionic conductivity of Na3MCl6. The formation of Na vacancies by aliovalent substitution considerably increased the ionic conductivity up to four orders of magnitude for pristine Na3MCl6, exhibiting similar to 10(-5) S cm(-1) for trigonal P31c and R3 phases. The formation of defects could further enhance the ionic conductivity of Na3MCl6, and the optimization of defect type and ratio can be helpful in developing superionic Na chloride SEs. The material design of Na3MCl6 in this study will provide fundamental guidelines for the development of novel sodium halide SEs for all-solid-state sodium-ion batteries.